2022
DOI: 10.1097/md.0000000000031355
|View full text |Cite
|
Sign up to set email alerts
|

Rare magnetic resonance imaging findings of intracranial solitary fibrous tumor: A case report

Abstract: Rationale: Solitary fibrous tumor (SFT) is a rare mesenchymal spindle cell tumor. SFT in the central nervous system (CNS) is rare. This case reports rare magnetic resonance imaging (MRI) findings of intracranial SFT (ISFT). Patient concerns: We report a 47-year-old female patient who was found to have weakness in her right limb with walking instability 2 months before the visit. Diagnoses: Based on imaging, the provisional diagnosis was meningiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…However, in our collective, it appeared rather inconsistently. In CNS-related locations, vascularized meningioma shows similar imaging patterns as meningeal SFTs and needs to be considered an important differential diagnosis [47,48]. Interestingly, a recent study by Liu et al demonstrated that DWI imaging (ADC1) could differentiate between SFT and atypical meningioma with high sensitivity and specificity [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our collective, it appeared rather inconsistently. In CNS-related locations, vascularized meningioma shows similar imaging patterns as meningeal SFTs and needs to be considered an important differential diagnosis [47,48]. Interestingly, a recent study by Liu et al demonstrated that DWI imaging (ADC1) could differentiate between SFT and atypical meningioma with high sensitivity and specificity [49].…”
Section: Discussionmentioning
confidence: 99%
“…This fusion leads to the pathological and immunohistochemical reversal, manifesting as nuclear STAT6 expression. Consequently, the distinction between the diagnoses of these two tumor types has become increasingly blurred [ 5 ].…”
Section: Introductionmentioning
confidence: 99%